PELATIHAN PEMBUATAN KERIPIK SAYUR DI KECAMATAN WANGI-WANGI SELATAN KABUPATEN WAKATOBI, PROVINSI SULAWESI TENGGARA - Rejeki, Sri; Harimu, La; L, Mariani (HIRONO : Jurnal Pengabdian Masyarakat, 2023)
Wangi-wangi Selatan is one of the areas in Wakatobi Regency which is rich in vegetables, especially kale, spinach, eggplant and bitter melon. However, it is only processed as a vegetable by direct cooking so it has a short shelf life. For this reason, training on making chips is carried out so that vegetables can be consumed for a long time and can also have economic value for the community, especially in Wangi Wangi Selatan sub-district. This training lasted for 7 days with a series of activities consisting of (a) counseling which was carried out for 2 days; (b) 4 days of training and (c) 1 day of activity evaluation. The results of this training are a) the utilization of local vegetables which can be processed into chips thereby increasing the community's economy; b) increasing community knowledge and skills on how to process vegetables into chips so as to extend and improve the family economy. The results of the evaluation of this training showed that the participants were very satisfied with the training on making vegetable chips and hoped to continue with different topics.